(untitled) (Castilla. Estudios de Literatura, 2018)
This paper aims to delve into the literary and publishing world of the Spanish intellectuals and artists exiled in New York through three axes: a brief analysis of the pre-war Hispanism that led to the reception of intellectuals during and after the Civil War; a review of the publishing situation of the war and immediate postwar period; and a further review of the most relevant Spanish magazines, publishers and bookstores ‒American, pre-war Spanish, and founded by exiled‒ of the later decades, being the exiled community already settled.